2016
DOI: 10.1530/jme-15-0293
|View full text |Cite
|
Sign up to set email alerts
|

Peptide production and secretion in GLUTag, NCI-H716, and STC-1 cells: a comparison to native L-cells

Abstract: ResearchPeptide production in GLP1-producing cell lines r e kuhre and others 56:3 (2016) 56, 201-211 Journal of Molecular Endocrinology 201-211Key Words AbstractGLUTag, NCI-H716, and STC-1 are cell lines that are widely used to study mechanisms underlying secretion of glucagon-like peptide-1 (GLP-1), but the extent to which they resemble native L-cells is unknown. We used validated immunoassays for 14 different hormones to analyze peptide content (lysis samples; n = 9 from different passage numbers) or pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 56 publications
4
71
0
Order By: Relevance
“…Several reports have suggested that, in addition to being derived from endocrine cells in the intestinal mucosa, both GLP‐1 and GIP may be produced locally within the pancreas, although in our laboratory we have never been able to identify GIP in murine or human pancreas extracts from healthy individuals (Holst and Hartmann, unpublished studies). Proglucagon is normally processed by prohormone convertase (PC) 1/3 in the intestinal L‐cell to produce GLP‐1 (and GLP‐2), while in the pancreatic α‐cells PC‐2 action produces glucagon . However, PC1/3 expression and fully processed GLP‐1 have been identified in rodent and human α‐cells, and islets in culture .…”
Section: Mechanism Of Actionmentioning
confidence: 84%
“…Several reports have suggested that, in addition to being derived from endocrine cells in the intestinal mucosa, both GLP‐1 and GIP may be produced locally within the pancreas, although in our laboratory we have never been able to identify GIP in murine or human pancreas extracts from healthy individuals (Holst and Hartmann, unpublished studies). Proglucagon is normally processed by prohormone convertase (PC) 1/3 in the intestinal L‐cell to produce GLP‐1 (and GLP‐2), while in the pancreatic α‐cells PC‐2 action produces glucagon . However, PC1/3 expression and fully processed GLP‐1 have been identified in rodent and human α‐cells, and islets in culture .…”
Section: Mechanism Of Actionmentioning
confidence: 84%
“…NCI-H716 cells are widely used in the study of GLP-1 secretion,17 and the presence of TGR5 receptor in NCI-H716 cells has been characterized 10. Therefore, we used NCI-H716 cells to investigate the effect of betulinic acid on GLP-1 secretion in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…90080 and 90060; Zaandam, Netherlands). For chromatography, 4 ml of a single pool of plasma from mice (n ϭ 20) and rats (n ϭ 27) were centrifuged (1,650 g, 4°C, 10 min), and the supernatant was fractionated by gel filtration as described previously (4,11,15).…”
Section: Biochemical Measurementsmentioning
confidence: 99%